Spatiotemporal Control of Neuronal Remodeling by Cell Adhesion Molecules: Insights From Drosophila - Meltzer, Hagar; Schuldiner, Oren (Frontiers in Neuroscience, 2022)
Developmental neuronal remodeling is required for shaping the precise connectivity of the mature nervous system. Remodeling involves pruning of exuberant neural connections, often followed by regrowth of adult-specific ones, as a strategy to refine neural circuits. Errors in remodeling are associated with neurodevelopmental disorders such as schizophrenia and autism. Despite its fundamental nature, our understanding of the mechanisms governing neuronal remodeling is far from complete. Specifically, how precise spatiotemporal control of remodeling and rewiring is achieved is largely unknown. In recent years, cell adhesion molecules (CAMs), and other cell surface and secreted proteins of various families, have been implicated in processes of neurite pruning and wiring specificity during circuit reassembly. Here, we review some of the known as well as speculated roles of CAMs in these processes, highlighting recent advances in uncovering spatiotemporal aspects of regulation. Our focus is on the fruit fly Drosophila, which is emerging as a powerful model in the field, due to the extensive, well-characterized and stereotypic remodeling events occurring throughout its nervous system during metamorphosis, combined with the wide and constantly growing toolkit to identify CAM binding and resulting cellular interactions in vivo. We believe that its many advantages pose Drosophila as a leading candidate for future breakthroughs in the field of neuronal remodeling in general, and spatiotemporal control by CAMs specifically.